2021
DOI: 10.1002/tpg2.20181
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulatory mechanism analysis of VvmiR156a–VvAGL80 pair during grapevine flowering and parthenocarpy process induced by gibberellin

Abstract: MicroRNA156 (miR156) is an important conserved miRNA family in plants. Recently, we revealed VvmiR156a could involve in the modulation of gibberellin (GA)‐mediated flower and berry development process of grapevine (Vitis vinifera L.). However, how to manipulate this process is unclear. For this, we used the GA‐induced grapevine parthenocarpy system to investigate the regulatory roles of VvmiR156a during this process. Here, we cloned the mature and precursor sequences of VvmiR156a in Wink grape and identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These results suggest that, just after the first and around the second GA 3 treatment period, the LBM berries have a higher sensitivity than the 'Delaware' berries. Although previous studies on seedless grapes with GA 3 treatment reported differential downstream gene expression of the DELLA proteins in GA signaling (Arro et al, 2019;Cui et al, 2020;Su et al, 2021), no study has yet focused on the high GA sensitivity of grape berries. LBM has characteristics of high GA sensitivity, therefore this study revealed that the high expression of the GA receptor gene may be responsible for the increased GA sensitivity.…”
Section: Gene Expression Analysis Following the Second Ga 3 Treatment...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that, just after the first and around the second GA 3 treatment period, the LBM berries have a higher sensitivity than the 'Delaware' berries. Although previous studies on seedless grapes with GA 3 treatment reported differential downstream gene expression of the DELLA proteins in GA signaling (Arro et al, 2019;Cui et al, 2020;Su et al, 2021), no study has yet focused on the high GA sensitivity of grape berries. LBM has characteristics of high GA sensitivity, therefore this study revealed that the high expression of the GA receptor gene may be responsible for the increased GA sensitivity.…”
Section: Gene Expression Analysis Following the Second Ga 3 Treatment...mentioning
confidence: 99%
“…Comprehensive gene expression analysis revealed that VvmiRNA159 regulates GA signaling in floral development (Wang et al, 2018). VvmiR156a negatively regulated VvAGL80 after GA 3 treatment, which promoted grape blooming (Su et al, 2021). Pre-bloom GA and auxin treatment facilitated grape berry parthenocarpy by downregulation of VvIAA9 and VvARF7 via DELLA (Jung et al, 2014).…”
Section: Introductionmentioning
confidence: 99%